FUNGSI KELOMPOK TANI DALAM PENYALURAN SARANA PRODUKSI PADI SAWAH DI DESA WUNGKOLO KECAMATAN WAWONII SELATAN KABUPATEN KONAWE KEPULAUAN - Mardin Mardin (JURNAL ILMIAH PENYULUHAN DAN PENGEMBANGAN MASYARAKAT, 2025)
The success of rice farming in Wungkolo Village is largely determined by the availability and distribution of effective means of production, technological and government support, and the strategic role of farmer groups in facilitating production needs and increasing farmer productivity. The objective of this study is to ascertain the role of farmer groups in the distribution of production inputs in Wungkolo Village, South Wawonii District, Konawe Islands Regency. The selection of informants was executed through the implementation of purposive sampling. The present study comprised a total of ten informants. The data presented herein were collected through the implementation of interviews, the structure of which was predicated upon a series of inquiries pertinent to the research topic. Furthermore, observation and documentation methods were employed to bolster the research findings. The focal point of this study was the function of farmer groups in the distribution of rice paddy production facilities. The data were analyzed using both descriptive and qualitative methods. The results of the study indicate that the function of farmer groups in the distribution of production facilities in Wungkolo Village is not yet functioning properly. This is evidenced by the distribution of fertilizers that are not yet of the right type and quantity, which is still less than what farmers need. The distribution of seeds can be considered effective if the distribution of seeds corresponds to the appropriate type and quantity. The distribution of pesticides is still not optimal in terms of type, quantity, and timing.